Nature‐reliant, low‐income households face the highest rates of woody‐plant encroachment in South Africa. Issue 4 (3rd June 2022) - White, Joseph D. M.; Stevens, Nicola; Fisher, Jolene T.; Archibald, Sally; Reynolds, Chevonne
Abstract: Woody‐plant encroachment is an under‐recognized consequence of land degradation. This phenomenon is common in rangeland ecosystems, where woody plants outcompete grasses, resulting in a shift to more wooded ecosystems. The consequences of this for livelihoods are most often damaging. Case studies at a local scale have shown negative consequences for ecosystem services and livelihoods, though few have considered these impacts over greater scales to find more generalizable patterns that are useful for governance structures at actionable levels. Here we make use of census data on household income and use of provisioning ecosystem services together with remote‐sensed woody‐plant encroachment data to perform the first country‐wide assessment at the municipal level across South Africa investigating correlations between woody cover change and (1) household income and (2) the use of provisioning ecosystem services use. We show that woody‐plant encroachment is greatest in municipalities with low income and a higher reliance on provisioning ecosystem services, specifically when woody cover was low. This reinforces a poverty trap by creating a positive‐feedback loop. For example, encroached landscapes with lower grass cover are more prone to overgrazing, decreasing fuel loads and further driving encroachment. This places more pressure on the remaining grass cover and decreases the provisioning of ecosystem services. Furthermore, our results allow us to rank the most affected municipalities based on income, reliance on provisioning ecosystem services and rates of woody cover change. We identify 16 municipalities requiring much‐needed interventions due to the risk of woody‐plant encroachment to natural resource‐reliant livelihoods. We suggest that interventions to reduce woody‐plant encroachment be targeted in low‐income communities, providing a win–win scenario for livelihoods and biodiversity. We recommend that woody‐plant encroachment be recognized as major form of land degradation and that restoration of encroached landscapes be prioritized within the UN Decade of Ecological Restoration 2021–2030. Read the free Plain Language Summary for this article on the Journal blog. Abstract : Read the free Plain Language Summary for this article on the Journal blog.